Era Revolusi Industri 4.0 : Peran Media Sosial Dalam Proses Pembelajaran Fisika di SMA - Armelia Yuniani; Dwi Irma Ardianty; Wal Asri Rahmadani (Program Studi Pendidikan Fisika FKIP Universitas Samudra, 2019)
Social media tools have become ubiquitous. We can see everyone use them all the time. The advancement of modern technologies tries its best to accommodate the needs from people, especially the younger generation or we can call it with The X Generation. This study deals with The Role of Social Media in the Physics Learning process in the Age of Industrial Revolution 4.0. The study was conducted using a literature review method. The results show that one social media that is Youtube influential in the development of physics learning in the era of the Revolution 4.0 industry. The top four reasons for using social media tools are for social engagement, direct communication, speed of feedback, and relationship building. Based on it, the author suggested some educational implications of some of those tools as a valuable resource for teaching and learning. Kata kunci: Sosial Media, Revolusi Industri 4.0, Generasi X